Employment of Mothers After Childbirth: French-German Comparison - Andrea Maria Weber; Charlotte Lauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper compares the work attachment of French and German women after childbirth. Both fertility and employment of mothers are higher in France than in Germany. Since the sample of mothers deciding on employment after a child is born might not be representative for all women, we take account of selectivity by explicitly modelling the childbirth decision of women. Furthermore, it proved essential to distinguish between part-time and full-time employment. Background characteristics appear to affect both the birth and the employment decisions in a different way in France and Germany. Some of the impacts can be related to different family policy regulations.
Keywords: D1; J2; 330; fertility; labour supply; Frauenerwerbstätigkeit; Mütter; Arbeitsangebot; Schätzung; Vergleich; Deutschland; Frankreich